Processing of misinformation as motivational and cognitive biases - Zhou, Yanmengqian; Shen, Lijiang (Frontiers in Psychology, 2024)
Misinformation can be broadly defined as false or inaccurate information created and spread with or without clear intent to cause harm. It travels fast and deep and persists despite debunking. It is well-documented that corrective messages and fact-checking efforts often fail to mitigate the effects or persistence of misinformation. In this article, we examine the persistence of misinformation as rooted in motivational and cognitive biases in information processing. While drawing on the frameworks of motivations that drive information seeking, sharing, and processing and various cognitive biases, we explicate mechanisms and processes that underlie the impact and persistence of misinformation. We conclude our article by discussing the potential utility of psychological inoculation as a prebunking strategy.